2017
DOI: 10.1097/aap.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of Ultrasound-Guided Injectate From the Adductor Canal to the Genicular Branch of the Posterior Obturator Nerve and the Popliteal Plexus

Abstract: Injection of 10 mL of dye into the distal part of the AC spreads into the popliteal fossa and colors the popliteal plexus and the genicular branch of the posterior obturator nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 35 publications
3
68
2
Order By: Relevance
“…The contribution of PON innervation is important and was reported in 82% of specimens (n=9/11) by Gardner,8 in 100% of specimens (n=10/10) by Runge et al ,18 and 100% of specimens (n=15/15) in the current study. Additionally, in the current study, the PON was found to course through the adductor hiatus consistent with previous studies 9 10.…”
Section: Discussionsupporting
confidence: 54%
“…The contribution of PON innervation is important and was reported in 82% of specimens (n=9/11) by Gardner,8 in 100% of specimens (n=10/10) by Runge et al ,18 and 100% of specimens (n=15/15) in the current study. Additionally, in the current study, the PON was found to course through the adductor hiatus consistent with previous studies 9 10.…”
Section: Discussionsupporting
confidence: 54%
“…Choosing the proximal or midpoints of the AC may not have given the same contrasting results. One potential drawback of the distal AC location is the observation of injectate spread into the popliteal fossa via the adductor hiatus which has been previously described 24. Despite attempts to maintain motor sparing effects by placing distal AC injections, motor nerve involvement may still occur due to spread toward the popliteal fossa.…”
Section: Discussionmentioning
confidence: 99%
“…The second case may support this theory that the adductor canal and the popliteal area is connected. Tran et al found that the dye injected from a medial IPACK approach tracked into the adductor canal and Runge et al found that dye injected in the adductor canal tracks in the popliteal area [7] [8]. If the nerve to the vastus medialis can be blocked with this same injection, it would avoid having to do a second block at the femoral triangle [27] or adductor canal [6] [11].…”
Section: Casementioning
confidence: 99%
“…The recent technique of ultrasound guided local anesthetic infiltration of the interspace between the popliteal artery and the capsule of posterior knee (IPACK) has shown promising results [3] [5] [6]. The technique involves a very selective block of the terminal sensory branches of the posterior aspect of the knee without the involvement of motor branches of the tibial and peroneal nerves leading to reduced pain without motor weakness [7] [8]. This leads to earlier ambulation, rehabilitation and recovery in various knee surgeries [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation